High-level information fusion management and systems design - Blasch, Erik; Bosse, Eloi; Lambert, Dale A. (Artech House, 2012)
This authoritative book serves a practical reference for developers, designers, and users of data fusion services that must relate the most recent theory to real-world applications. This unique volume provides alternative methods to represent and model various situations and describes design component implementations of fusion systems.